HOW THE COVID-19 CRISIS IS AFFECTING CUSTOMERS’ INTENTION TO USE ISLAMIC FINTECH SERVICES: EVIDENCE FROM INDONESIA - Dety Nurfadilah; Sudarmawan Samidi (Bank Indonesia, 2021)
The objective of this study is to investigate the factors that are affecting customers’ intention to use Islamic FinTech services during the Covid-19 crisis. It expands the technology acceptance model (TAM) by adding government support as a new variable for the context of Islamic FinTech services during the pandemic. Using TAM as a framework, we propose a model outlining the impact of government regulation, perceived usefulness, perceived ease of use, perceived trust, and user innovativeness on consumer attitude behaviour and the intention to use Islamic FinTech services, such as payment and peer-to-peer lending. 220 sets of data were collected from an online survey and analysed using partial least squares-structural equation modelling (PLS-SEM). The results show that government support for Islamic FinTech during the Covid-19 pandemic has had an indirect impact on attitude behaviour in using Islamic services through perceived ease of use and perceived usefulness. Attitude behaviour was found to have an impact on intention.